Rambert Dance Company at 75 - Gilbert, Jenny (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Rambert Dance Company. PALABRAS CLAVE: Rambert Dance Company, history, Christopher Bruce.
Dentro del apartado "It was the best of times, it was the worst of times"...A Tale of Two Companies.